Feynman's space-time view in quantum electrodynamics. (June 2022) - Forgione, Marco
Abstract: The present paper offers a reconstruction of what Feynman calls: "the overall spacetime view". To provide some background, I will rehearse Feynman's works on the absorber theory of radiation and on path integrals to emphasize the rejection of the so-called "customary view". Afterward, I will argue that Feynman's doctoral thesis was instrumental in developing the idea of enclosing a given quantum system into a spacetime boundary. This will be later applied to the path integral formulation and will play a substantial role in the use of asymptotic states in the theory of positron. It is in this latter work that Feynman uses the expression: "overall spacetime view", referring to the necessity of looking at all the possible quantum phenomena happening within the spacetime boundary. In the last part of the paper, I analyze how such a view applies to Feynman's work on quantum electrodynamics and Feynman diagrams.